2009
DOI: 10.5271/sjweh.1361
|View full text |Cite
|
Sign up to set email alerts
|

The Occupational Safety and Health Scorecard – a business case example for strategic management

Abstract: Objective Human resources and health issues are crucial in terms of corporate competitiveness. However, systematic, continuous and strategically aligned occupational safety and health (OSH) management is scarcely applied in companies. One major reason for this could be the lack of generally accepted and standardised OSH control methods. Our objective was thus to conceptualize a method by which qualitative factors such as human resources and OSH aspects contribute to the performance or value-added layer of an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…The fact that small firms constitute 96% of the construction industry means that small firms are faced with the problem of having the highest rate of accidents in the construction industry. This situation according to Koper, Moller, & Zwetsloot (2009) impacts negatively on the physical, mental and social wellbeing of employees, increase cost of production, make firms less competitive, and reduce small construction firms' profitability, growth, and contribution to the Australian economy. O'Toole (2002) argues that management commitment to WHS plays a key role in the successful development and implementation of safety programs and improving safety performance, which has a positive relationship with competitive advantage and overall organisational performance (Rechenthin, 2004).…”
Section: Research Problemmentioning
confidence: 99%
“…The fact that small firms constitute 96% of the construction industry means that small firms are faced with the problem of having the highest rate of accidents in the construction industry. This situation according to Koper, Moller, & Zwetsloot (2009) impacts negatively on the physical, mental and social wellbeing of employees, increase cost of production, make firms less competitive, and reduce small construction firms' profitability, growth, and contribution to the Australian economy. O'Toole (2002) argues that management commitment to WHS plays a key role in the successful development and implementation of safety programs and improving safety performance, which has a positive relationship with competitive advantage and overall organisational performance (Rechenthin, 2004).…”
Section: Research Problemmentioning
confidence: 99%
“…Consequently, good practice might include reporting consequences in multiple ways, particularly in cases where important outcomes (eg, health, worker morale, job satisfaction, health perceptions, product/ service quality, and client relations) are difficult to monetize. A recent case study demonstrated that OSH interventions can contribute significantly to various performance outcomes (17).…”
Section: Economic Evaluations Should In Addition To Considering Effimentioning
confidence: 99%
“…Small business contributes significantly to this statistics as it constitutes 96% of the total number of business that operate within the construction industry (Australia Parliament House (APH), 2016). This situation according to Koper, Moller and Zwetsloot (2009) impacts negatively on the physical, mental and social wellbeing of employees, increase cost of production, and make firms less competitive.…”
Section: Introductionmentioning
confidence: 99%